Ultrasonic-assisted preparation and characterization of sheepskin gelatin films modified with konjac glucomannan - Hasdar, Muhamad; Nalinanon, Sitthipong; Kittiphattanabawon, Phanat; Sriket, Chodsana (My University, 2026)
Gelatin derived from sheepskin (GSS) is a promising biomaterial for edible, biodegradable films, but exhibits poor water resistance, mechanical weakness, and brittleness. This study developed ultrasound-assisted composite films based on GSS and konjac glucomannan (KG; 0–75% w/w) to enhance their functionality. The ultrasonic treatment (40 kHz, 15 min) improved homogeneity and reduced structural defects. KG incorporation significantly increased film thickness from 0.031 mm to 0.038 mm and tensile strength from 0.5118 MPa to 0.9601 MPa, while reducing water vapor transmission from 2.6974 g m⁻² day⁻¹ to 1.7304 g m⁻² day⁻¹ and water activity from 0.4526 to 0.3084. Swelling decreased from 4.77% to 3.82%, whereas water resistance improved from 95.23% to 96.18%. The optimal formulation (25% KG) provided a balance between strength, flexibility, and hydrophobicity. FTIR confirmed intermolecular hydrogen bonding between GSS and KG, and ultrasound promoted uniform dispersion and denser microstructures. These findings highlight ultrasound-assisted GSS/KG films as sustainable, protein-polysaccharide-based materials with superior physicochemical and barrier properties for eco-friendly food packaging applications.
Keywords: Biodegradable packaging; Gelatin-based films; Konjac glucomannan; Protein modification; Ultrasonication